2000
DOI: 10.1093/ejo/22.5.509
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between occlusion and satisfaction with dental appearance in orthodontically treated and untreated groups. A longitudinal study

Abstract: The aims of this study were to assess the relationship between occlusion, satisfaction with dental appearance, and self-esteem at the ages of 11 (T1) and 15 years (T2), and to study perceived treatment effects. Separate questionnaires were completed by children and their parents to determine their attitude. The dental casts of 224 children were collected at T1 and T2, and assessed by the Aesthetic Component (AC) and Dental Health Component (DHC) of the Index of Orthodontic Treatment Need (IOTN), and Peer Asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 20 publications
1
119
0
3
Order By: Relevance
“…2,6 This can be explained by the different motivations and expectations of patients receiving orthodontic treatment. Most studies report functional, esthetic, and social reasons as the main motives to seek orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…2,6 This can be explained by the different motivations and expectations of patients receiving orthodontic treatment. Most studies report functional, esthetic, and social reasons as the main motives to seek orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Birkeland et al 30 examined the relationship between dental appearance and satisfaction longitudinally in orthodontically treated and untreated individuals. They found that although 92 percent of treated children's parents were sure that they would choose to let their child go through the same treatment again, only 34 percent were sure that the treatment result was of a positive importance to their child's social skill, 23 percent that it was likely that it would have a positive influence on the future choice of mate and 19 percent that it would be of significance for their child's future working career.…”
Section: Discussionmentioning
confidence: 99%
“…Patient satisfaction after orthodontic treatment is influenced by a number of factors 7,8,14,15 . The investigations of patient satisfaction after orthodontic treatment have shown a wide range of satisfaction levels [16][17][18] . The use of different questionnaires to assess satisfaction makes comparison with other studies difficult.…”
Section: Methodsmentioning
confidence: 99%